(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2022)
Background: Benign cystic teratoma or dermoid cysts are germ cell tumour of the ovary which accounts for 20-25% of all ovarian tumour and are bilateral in 10-15% of cases. These tumour have a low incidence of malignancy, reported as 1-3%. The aim of the study is to determine the safety and efficacy of the laparoscopic management of ovarian dermoid cyst over laparotomy. Methods: This prospective study was conducted in the Department of Obstetrics and Gynaecology, BIRDEM-II General Hospital, from January 2013-December 2018. During the study period, a total of sixty subjects were included for comparison. Thirty patients were selected for laparoscopic ovarian cystectomy and another thirty patients were selected for laparotomy. They were randomly selected for the procedures. Result: Thirty patients with ovarian dermoid cyst undergoing laparospic surgery were compared with thirty patients with ovarian dermoid cyst undergoing laparotomy in respect to selection criteria, surgical procedures, operation time, blood loss, hospital stay and outcome of operation. Although the operation time for ovarian cystectomy performed by laparoscopic surgery was slightly longer (62.15 ± 16.3 min, mean ± SD) than by laparotomy (50 ± 16.20 min, p < 0.52), blood loss is smaller and hospital stay is shorter in laparoscopic group than laparotomy. Conclusion: The laparoscopic approach is generally considered to be the gold standard for the management of dermoid cyst. We believe that laparoscopic management of dermoid cyst may be a safe and beneficial procedure when performed by experienced surgeon. Bangladesh J Obstet Gynaecol, 2020; Vol. 35(2): 107-111